2017
DOI: 10.5897/ajb2015.14885
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of monocrotophos by bacteria isolated from soil

Abstract: Bacteria were isolated by enrichment culture technique from groundnut (Arachis hypogaea L.) soils and tested for their ability to degrade monocrotophos in mineral salts medium under aerobic conditions in the laboratory. Based on some of the morphological and 16S rRNA gene sequence analysis, the isolates were identified as Rhodococcus phenolicus strain MCP1 and Rhodococcus ruber strain MCP-2. The initial (0-day) recovery of monocrotophos in the culture medium was 94%; and by the end of 4 th day, about 21% of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…investigated cyclohexanone degradation using Pseudomonas with phenol production. The metabolite detected in GC MS during monocrotophos degradation in the present study is acetamide, N-acetyl N-methyl, which were also detected as an intermediate metabolite of monocrotophos degradation bySrinivasulu et al (2017) [18]. According toAcharya et al (2015) [3], N-methylacetoacetamide was degraded to methylamine and carbon dioxide and these products were detected during monocrotophos degradation using isolate B. subtilis KPA-1.…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…investigated cyclohexanone degradation using Pseudomonas with phenol production. The metabolite detected in GC MS during monocrotophos degradation in the present study is acetamide, N-acetyl N-methyl, which were also detected as an intermediate metabolite of monocrotophos degradation bySrinivasulu et al (2017) [18]. According toAcharya et al (2015) [3], N-methylacetoacetamide was degraded to methylamine and carbon dioxide and these products were detected during monocrotophos degradation using isolate B. subtilis KPA-1.…”
mentioning
confidence: 51%
“…Thus, degradation analysis revealed that consortium is more effective than pure bacterial isolates for monocrotophos degradation. Another study found that Rhodococcus phenolicus and R. ruber mediated degradation ranged from 30% to 45% after 96 h of incubation [18]. After 17 days of incubation, Sidhu et al (2015) [6] reported 67.8%, 16.58%, and 6.67% degradation using isolated P. synxantha, B. subtilis, and S. enterica.…”
Section: Monocrotophos Degradationmentioning
confidence: 98%
See 1 more Smart Citation
“…Screening of Isolates for PGPR Traits: The actinobacterial isolates were screened for PGPR traits [16][17][18][19][20] .…”
Section: Methodsmentioning
confidence: 99%
“…70 Other bacterial strains isolated from pesticide-polluted soil, including Bacillus licheniformis, Bacillus subtilis, Pseudomonas stutzeri, Rhodococcus phenolicus, and Rhococcus ruber have also demonstrated substantial efficiency in breaking down monocrotophos. 71,72 Moreover, Paracoccus sp., isolated from sludge, exhibits a rapid monocrotophos degradation rate, removing approximately 80% of the substance within a mere 6 hours of incubation, and it has been found to also be effective in breaking down the amide group found in certain herbicides. 73 Further, two other effective agents in the degradation of monocrotophos are Clavibacter michiganense subsp.…”
Section: Monocrotophos Breakdownmentioning
confidence: 99%